In vitro Study of Elution Characteristics of Antiviral Drugs Immersed in Bone Cement - E. O. Peretsmanas; A. A. Artyukhov; I. A. Gerasimov; V. S. Zubikov; T. E. Tyulkova; Ya. A. Rukin (Туберкулез и болезни лёгких)
The objective: to assess elution characteristics of certain antiviral drugs immersed in bone cement samples and placed in a liquid medium to determine the fundamental possibility of using such systems.Subjects and Methods. For the in vitro study, dispersed ART formulation mixed with bone cement were used. To study kinetics of drug elution, a spectrophotometry was used.Results. It was found out that raltegravir, emtricitabine and lamivudine possessed satisfactory thermostability and elution parameters thus allowing their use in a mixture with bone cement. The results demonstrated the fundamental possibility of developing systems with controlled release of these drugs immersed in bone cement and placed into a liquid medium.